ANALISIS INDEKS KEKERINGAN METODE STANDARDIZED PRECIPITATION INDEX (SPI) DAN PENGARUHNYA TERHADAP PRODUKTIVITAS PADI DAN JAGUNG - Dewi Masruroh; Cahyoadi Bowo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Drought is one of the most significant impacts of the climate on agriculture, especially food crops. Standardized Precipitation Index (SPI) is an Index for droughts. The research objective was to study the relationship of SPI values to the productivity of rice and corn crops in the Situbondo district. The result showed that the value of the SPI time scale at three months is the most appropriate for the observed productivity of rice and corn. The SPI value significantly correlated with the productivity of rice plants in the Jatibanteng and Arjasa districts but did not significantly affect the productivity of corn in the Mlandingan and Situbondo districts. Furthermore, the El-Nino phenomenon reduced the rice productivity up to 3.9% and the corn productivity up to 48.1%. The La-Nina phenomenon reduced rice productivity up to 26.0% but increased the productivity of corn up to 81.7%.